Profil Efikasi Diri Pengambilan Keputusan Karir pada Mahasiswa Perguruan Tinggi - Rega Arbyan Permana; Cucu Arumsari; Dewang Sulistiana (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
This study aims to identify the profile of career decision-making self-efficacy among students at Universitas Muhammadiyah Tasikmalaya based on categorization, specific aspects, and comparisons between male and female students. This research employs a quantitative descriptive method to reveal the general overview of CDMSE among university students. The population of this study consists of students from the 2022 cohort at Universitas Muhammadiyah Tasikmalaya. The sample includes 260 students selected using simple random sampling. The results show that, in general, the CDMSE profile falls into the moderate category, with 60.77% (158 students). The highest aspect identified is self-appraisal. Based on gender, male students demonstrate slightly higher CDMSE levels compared to female students. However, the One-Way ANOVA analysis result of 0.414 > 0.05 indicates that there is no significant difference in CDMSE between male and female students.